OC03 : Visceral responses to direct electrical stimulation of the Human cortex. (March 2022) - Soulier, H.; Mauguière, F.; Catenoix, H.; Montavont, A.; Isnard, J.; Rheims, S.; Mazzola, L.
Abstract : Background: Visceral and emotional sensations (VES) are frequently reported during epileptic seizures. To date, the underlying mechanisms and the location of brain areas involved in the processing of these sensations remain unclear. The aim of our study is to characterize the type and frequency of VES evoked by electrical stimulations performed all over the cortical mantle and to assess whether they might be related to specific brain structures. Methods : We reviewed 12, 088 bipolar stimulations performed in 203 patients using stereotactically implanted depth electrodes, during the presurgical evaluation of drug-refractory epilepsy, at Neurological Hospital in Lyon (France). VES were divided into viscero-sensitive (feelings in the throat, thorax or abdomen), viscero-vegetative (flush, nausea, feeling of tachycardia and dyspnea) and viscero-psychic sensations (fear, anxiety). Univariate analysis and then conditional logistic regression were used to assess the association between VES and localization of the stimulated contacts. Results : 543 stimulations evoked VES (4.26%). Stimulations of insulo-limbic structures (amygdala, anterior and posterior insula, anterior and mid-cingulate cortex, hippocampus and parahippocampus) were significantly more associated with VES than those of extra limbic structures (p<0.0001). Preferential implication of certain brain structures, depending on the type of visceral responses was evidenced: temporo-mesial structures (amygdala, hippocampus and parahippocampus) and insula for viscero-sensitive sensations; amygdala, insula and mid-cingulate cortex for viscero-vegetative sensations; temporo-mesial structures and anterior cingulate cortex for emotional sensations. Conclusion : These data can help to localize the epileptogenic zone in seizures with visceral sensations, and also bring insights in the discussion on the mechanisms of interoception.